Efficacy of Cognitive-Behavioral Therapy in Optimizing Counseling Outcomes for Fast Remission of Social Anxiety with Panic Attacks - Sonia Mukhtar; Shamim Mukhtar; Fatima Naeem; Waleed Rana (National Scientific Medical Center, 2024)
Aims: The case study evaluates the efficacy of Cognitive Behavioral Therapy in optimizing counseling outcomes for social anxiety and panic attacks within an academic setting. Counseling sessions were conducted with a 23-year-old female client over a four-month period at T.S Government College. Method: The study utilized a single case study design A-B-A. The client presented with symptoms of social anxiety and panic attacks, impacting various aspects of her life including academic performance, interpersonal relationships, social interactions and family dynamics. Results: Cognitive Behavioral Therapy techniques including Cognitive Restructuring, Social Skills Training, Role Play and Role Reversal, and Systematic Desensitization through Gradual Exposure, were implemented over 8 sessions. Assessment tools including pre-post ratings, behavioral observations and therapy blueprints were utilized to assess the severity of social anxiety. Conclusion: A significant decrease in the severity of social anxiety and panic attacks based on both subjective self-reporting and objective observations suggesting Cognitive Behavioral Therapy as an approach of counseling for individuals with social anxiety with panic attacks in educational setting. Keywords: Cognitive Behavioral Therapy, case study, case report, social anxiety, panic attacks, cognitive restructuring, systematic desensitization, role play, role reversal, social skills training